PENGARUH KEPERCAYAAN DIRI TERHADAP KOMUNIKASI INTERPERSONAL (STUDI MAHASISWA/I YANG MENJALANI KEHIDUPAN PABBAJITA) DI STIAB JINARAKKHITA - Gesti Tri Rahmawati; Indra Yana; Dwi Ratna Sari; Komang Sutawan (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the effect of self-confidence on the interpersonal communication of students who live the life of Pabbajita at STIAB Jinarakkhita in the study of Buddhism. Self-confidence is an attitude where a person is confident in his abilities so that he feels polite in interacting with others. In interpersonal communication, self-confidence is also needed so that interpersonal communication can run well and smoothly. This type of research is a quantitative research using a correlational approach. The subjects used in this study were 30 students who lived Pabbajita life at STIAB Jinarakkhita. The results showed that there is a positive influence of self-confidence on interpersonal communication. The magnitude of the influence of self-confidence is 64,2% while 35,8% of self-confidence is influenced by other variables outside the study.